PENGARUH LKS TERINTEGRASI MATERI BENCANA BANJIR PADA KONSEP BENDA TEGAR DAN FLUIDA TERHADAP HASIL BELAJAR FISIKA SISWA DALAM MODEL CASE BASED LEARNING - Destriayu Vasista (Universitas Negeri Padang, 2014)
This experiment is based on the problem that student learning outcomes are still under standard. It happens because the learning is not related with events that often experienced by students. The purpose of experiment is to investigate the effects of student work sheets integrated by flood material to the physics student learning outcomes using Case Based Learning Model. Type of research is a Quasi Experiment. Design of research is randomized Control Group Only Design. The population of research is all the student of grade XI science in SMAN 2 Painan enrolled in the academic year 2013/2014. The sample is selected by cluster random sampling technique; the sample is consisted of XI Science 4 as experiment class and XI Science 3 as control class. The data of research are physics learning outcomes include cognitive domain, affective domain, and psychomotor domain. The technique of collecting data for cognitive is essay; for affective and psychomotor is observation sheet. Analysis of data uses two similarity average test for the cognitive domain, affective domain, and psychomotor domain. Result of data analysis is average student learning outcomes, 71,07 for experiment class and 64,15 for control class toward cognitive domain; 73,3 for experiment class and 70,03 for control class toward affective domain; 78,92 for experiment class and 75,36 for control class toward psychomotor domain. The result of two similarity average test shows t count > t table. The conclusion of research is hypothesis that there is significant effects of Student work sheet integrated by flood material to the physics student learning outcomes using Case based Learning model can be accepted on the real level of 0.0